DENTISTS’ PLANNING PREFERENCES FOR REMOVABLE DENTURES AND OBSERVED COMPLICATIONS IN THEIR PATIENTS: A QUESTIONNAIRE-BASED STUDY - YILDIRIM, Levent (Brazilian Journal of Implantology and Health Sciences, 2024)
ABSTRACT Purpose: The aim of this study is to examine the practice preferences of general dentists regarding removable partial denture (RPD) treatment, to determine various complaints and problems observed in their patients, and to investigate the relationship of these cases with the experiences and institutional working methods of the dentists. Study design: A questionnaire-based study. Materials and Methods: A 13-question questionnaire was administered to 161 general dentists between October 1 and November 31, 2019. The questionnaire consists of questions regarding the dentists’ RPD treatment practice preferences, complaints of the patients after the application of these dentures, and the complications that develop. Results: The most common complaints of patients using clasp-retained dentures were; loosening of the clasp (77.0%), caries in the abutment teeth (50.9%), clasp fracture (47.2%) and aesthetic problems (44.1%). The most common complaint in precision attachment dentures was determined to be loosening of the retainer element (70.2%). The most common complication in such dentures was reported as loosening of the retainer element (67.1%). When the professional experiences of the dentists are examined; the rate of gum problems in patients using clasp retained and precision attachment RPD by dentists with 10 years or less of experience was found to be significantly higher in both types of dentures compared to the patient rates of dentists with more than 10 years of experience (p=0.012). Conclusion: The findings obtained from the present study show that the majority of general dentists prefer clasp retained RPDs, and the most common problems encountered in these dentures are loosening of the retainer element, caries and mobility in the support teeth. In addition, it was observed that dentists with less experience and working in private clinics encountered more complaints and problems in patients who had RPD treatment. Keywords: Dentist, removable partial denture, precision attachment, clasp retained, questionnaire.